PENERAPAN KONSEP PEKARANGAN PANGAN BERGIZI DALAM MENUNJANG KEBUTUHAN GIZI MASYARAKAT - Octaviane, Maria; Syamsul Rahman; Helda Ibrahim (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the implementation of the Nutritious Food Yard Concept (Pekarangan Pangan Bergizi/P2B) in supporting community nutritional needs in Lembang Ke’pe’ Tinoring, Mengkendek District, Tana Toraja Regency. The research was motivated by the suboptimal utilization of home yards as sources of nutritious food, despite their potential to support household food security. The study employed a quantitative descriptive method involving 70 farmer group members participating in the P2B program, selected using purposive sampling. The variables examined included the implementation of the P2B concept and the fulfillment of community nutritional needs, with indicators covering yard size, group activity, cultivation techniques, household consumption of yard produce, and reduction in food expenditure. The findings indicate that most respondents were in the productive age group (41–50 years), had secondary education levels, and owned medium-sized yards (120–400 m²). The use of home yards significantly improved household food availability, increased the consumption of vegetables and fruits, and reduced food expenditure. Internal factors such as yard size and group participation were found to significantly influence program success, while external factors included agricultural extension and technical assistance. Overall, the application of the Nutritious Food Yard Concept contributed positively to household food security and the fulfillment of community nutritional needs in the study area.